Efficacy of Topical and Systemic Vitamin E in Preventing Chemotherapy-Induced Oral Mucositis - Mafi, Ahmad Reza; Azizi, Arash; Alirezaei, Somayeh; Pedram, Pardis (Reports of Radiotherapy and Oncology, 2015)
Background: There is still no consensus regarding the optimum treatment of chemotherapy-induced oral mucositis and its management is still mainly supportive. Vitamin E has been shown to be effective in reducing the symptoms of oral mucositis. Objectives: Aim of this study was to assess the efficacy of prophylactic systemic and topical vitamin E in reducing the signs and symptoms of oral mucositis in patients receiving chemotherapy. Patients and Methods: We conducted a placebo-controlled randomized clinical trial among 76 patients with a hematologic malignancy treated with chemotherapy. Patients were randomly assigned into three groups: supplementation with vitamin E paste (group 1) and 200 mg/d vitamin E pills (group 2). Group 3 received placebo paste, identical in appearance and taste to the vit E paste, but consisting of the vehicle only. Patients were advised to use the administered medication from two days before each cycle of chemotherapy till at least 20 days after completion of each cycle. Oral exam was performed 10-14 days after each cycle of chemotherapy. Results: Patients in group 2 and 3 did not show any difference in degree of mucositis or severity of pain. However, after the second cycle, patients who were treated with topical vitamin E showed significantly less oral pain, and had fewer cases of severe mucositis compared to groups 2 and 3. Conclusions: Topical vitamin E could be beneficial in reducing the severity of oral mucositis, but no therapeutic gain would be achieved by using systemic vitamin E in this regard.